Leadership styles in Heredia’s educational institutions: a comparative study among management and teaching staff (Innovaciones Educativas, 2020)
Leadership is a fundamental feature of institutions in general and the field of education in particular. The leadership style can directly influence the organizational climate of the institutions, promoting a good performance in the administrative and teaching staff, as well as in the students. A quantitative methodology was used in the present research, with an ex-post-facto and cross-sectional design, applying the Multifactor Leadership Questionnaire (MLQ) to a stratified probabilistic sample of 125 managers and 584 teachers of public schools of the Regional Directorate of Education of Heredia. The main outcomes show high scores in the transformational and transactional leadership styles and low in the laissez-faire style. Likewise, significant differences have been detected between the self-perception of headteachers and teachers concerning these styles. Aspects related to tasks, beliefs, self-confidence, problem-solving set off with different perceptions between both groups of professionals. This dissociation from the same reality can interfere in the management carried out by school principals regarding common goal and objectives fulfillment. The legitimation of the educational community towards the leadership exercised by headteachers is a key element for effective educational organization management.
Keywords: Leadership; educational management; educational administration; educational personnel; education